Environmental influences on the production of pre-implantation embryos - Diercks, Ann-Kathrin; Schwab, Anna; Rittgen, Werner; Heuss, Edgar; Schenkel, Johannes (Theriogenology, 2010)
Generation and cryopreservation of transgenic mice depend on reliable and continuous production of pre-implantation embryos. To suppress circannual and circadian rhythms driving the physiological and sexual behaviour of free living animals, laboratory animals are housed under standardized conditions. It remains to be elucidated if the artificial climate can cover all environmental effects. Here, we report that the humidity in an animal facility affects the embryo yield. The weather at the location of the facility, especially the temperature, influences the climate within an animal facility; weather peaks are obviously covered in part only, even if the facility is equipped with a powerful air-conditioning supply. Subsequently, external weather changes interact with the environment within the facility, influencing the production of embryos. Furthermore, noise and/or vibrations as generated by construction works, negatively affect the embryo yield.